Persistence in Tax Revenues: Evidence from Some OECD Countries - Guglielmo Maria Caporale; Silvia García Tapia; Luis Alberiko Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper examines persistence in tax revenues in a set of 21 OECD countries over the period 1965-2021 using long-range dependence techniques based on fractional integration. The results imply that there are only a few cases of mean reversion: one for total revenue (Switzerland); three for VAT (Belgium, Italy, and Spain), and six for tax on income (Austria, Belgium, Finland, Spain, Sweden and USA). The analysis is also carried out for inflation in the same set of countries. Again the I(1) hypothesis cannot be rejected in most cases, mean reversion only occurring in Korea, Iceland, Norway and Sweden. However, stronger evidence of mean reversion is found for the differences between the three original tax series and inflation compared to the tax series themselves, which points to the existence of a linkage between taxation and inflation, especially in the case of VAT and tax on income.
Keywords: C13; C22; 330; revenues; taxes; persistence; fractional integration; long memory